(untitled) (Global Journal of Science Frontier Research, 2018)
The present study on temperature and pH of two Islands of Andaman during the period 2009 to 2011 suggested that the temperature increased during the year 2010 compared to the years 2009 and 2011. Moreover, a unique kind of change were noted during the years 2009, 2010, where in the bottom water (10m) exhibited comparatively higher temperature than the surface waters in both the Islands. The bottom water moved upward vertically to the surface after a 30 day period, probably due to upwelling. Earlier reports on upwelling in the Bay of Bengal and the Andaman Sea suggested that atmospheric circulation and temperature were the foremost cause for coastal upwelling. However, the above two factors did not have much significance due to the smaller surface area of these Islands. The submarine groundwater discharge could be playing a pivotal role in coastal upwelling. The groundwater discharge can lead to displacement of water mass due to the difference in physico-chemical properties, resulting in the upward movement of it towards surface over a 30 day period. This phenomena was more prominent during the nonrainy season. These inferences should be further strengthened by continuous monitoring of the nearshore waters for a larger time scale.